Durability of mortar and concrete made up of pozzolans as a partial replacement of cement: A review. (30th July 2016) - Hossain, M.M.; Karim, M.R.; Hasan, M.; Hossain, M.K.; Zain, M.F.M.
Highlights: Durability of mortar/concrete containing blended pozzolans and cement is reviewed. Water absorption, permeability, sorptivity and shrinkage are discussed. Chloride, carbonation, corrosion, sulfate and acid resistance are highlighted. Durability of blended mortar/concrete is compared with the ordinary one. Based on past researches, few potential studies are suggested for future research. Abstract: In recent years, researchers have been focusing on developing more sustainable cementitious systems in order to curb the negative environmental impacts and disintegration of concrete structures associated with ordinary Portland cement (OPC). Several attempts have been made to develop sustainable binders through the use of pozzolans such as slag, fly ash (FA), palm oil fuel ash (POFA), metakaolin (MK), silica fume (SF), rice husk ash (RHA) etc. with a relatively larger amount of replacement of OPC. A certain level of cement replacement with those pozzolans is highly advantageous in terms of cost, energy efficiency, ecological and environmental benefits as well as durability properties. More recently, researchers have mainly focused on the possibility of practical use of pozzolans (Slag, POFA, FA, SF, MK and RHA) as a partial replacement of cement in quest for improved long-term strength and durability properties. Based on published documents, this paper reviews the current state of knowledge on durability of mortar and concrete made up of pozzolans as a partial replacement of cement. A number of important properties of the made mortar and concrete among others compressive strength, sorptivity, permeability, water absorption, chloride penetration, sulfate resistance, carbonation, drying shrinkage, corrosion resistance, and resistance to acid attack have been discussed here. Finally, several potential studies have been suggested for the future research.